MUSIQA MASHG‘ULOTLARIDA CHOLG‘U ASARLARINI O’RGATISH ORQALI O‘QUVCHILARDA MUSIQIY-ESTETIK DIDNI SHAKLLANTIRISHNING TASHKILIY-PEDAGOGIK MEXANIZMLARI - Madrimov, B.X.; Samatova, D.S.; Omanqulova, Sh.N. (SCIENCE and SOCIETY, 2023)
The article reveals the pedagogical foundations and mechanisms for the formation of musical and aesthetic taste in students through the introduction of teaching musical instruments in music lessons, which are the heritage of folk music. At the same time, this is a wide range of opportunities for shaping the musical and aesthetic taste of students by accustoming them to observe the Teacher-Student traditions, increasing their spirituality and love for our national songs, Motherland, family and people.